Five new species of Pseudachorutes (Collembola: Neanuridae) from Mexico - José G. Palacios-Vargas; Erika Rivero-Sánchez; Yan Gao; Margarita Ojeda (Revista Mexicana de Biodiversidad)
As a result of 40 years of work and many projects on soil fauna and especially springtails, a collection of edaphic microarthropods has been established at the Facultad de Ciencias, UNAM, and has the name of “Colección de ácaros y colémbolos del Laboratorio de Ecología y Sistemática de Microartrópodos”. During the revision of material belonging to the subfamily Pseudachorutinae kept in the Collembola collection, we obtained 581 records of 28 species of Pseudachorutes, from 20 states and 62 localities from Mexico. Three are new records: P. ca. algidensis, P. ca.crassus y P. reductus, and 5 new species from soil, litter and epiphytic plants in Mexico are described and illustrated herein: P. tabasquensis sp. nov., P. mexicanus sp. nov., P. chichinautzin sp. nov., P. tillandsiodes sp. nov., and P. veracruzensis sp. nov.